2016
DOI: 10.1080/09553002.2016.1234725
|View full text |Cite
|
Sign up to set email alerts
|

Dose assessment intercomparisons within the RENEB network using G0-lymphocyte prematurely condensed chromosomes (PCC assay)

Abstract: Purpose: Dose assessment intercomparisons within the RENEB network were performed for triage biodosimetry analyzing G 0 -lymphocyte PCC for harmonization, standardization and optimization of the PCC assay. Materials and methods: Comparative analysis among different partners for dose assessment included shipment of PCC-slides and captured images to construct dose-response curves for up to 6 Gy c-rays. Accident simulation exercises were performed to assess the suitability of the PCC assay by detecting speed of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
3
37
0
4
Order By: Relevance
“…A similar study was performed with the results of the second PCC ILC based on the results presented in Terzoudi et al (2016). For this ILC, two samples per dose were distributed to the participants (samples respectively labelled Re5a, Re5b, Re6a and Re6b).…”
Section: Re-evaluation Of Results Of the Second Reneb Ilcmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study was performed with the results of the second PCC ILC based on the results presented in Terzoudi et al (2016). For this ILC, two samples per dose were distributed to the participants (samples respectively labelled Re5a, Re5b, Re6a and Re6b).…”
Section: Re-evaluation Of Results Of the Second Reneb Ilcmentioning
confidence: 99%
“…For the second ILC, all samples were irradiated in air at the same facility with dosimetric references expressed in terms of air kerma, whereas some participants reported results in terms of absorbed dose in water. This fact is not taken into account in the analysis provided in papers submitted in this issue Oestreicher et al 2016;Terzoudi et al 2016). …”
Section: Re-evaluation Of Data Of the Second Ilcmentioning
confidence: 99%
See 1 more Smart Citation
“…Training courses were mainly dedicated to DCA, FISH, MN, cH2AX and PCC assays. After completion of the practical training, a second inter-comparison was performed also on irradiated samples Oestreicher et al 2016;Terzoudi et al 2016). The results showed the benefits of training sessions.…”
Section: Education and Trainingmentioning
confidence: 99%
“…The first intercomparison focused on biological assays (DCA; FISH; MN and PCC) has shown that the majority of RENEB partners reached the criteria for biological dosimetry indicator scoring and dose estimation: the calculated 95% confidence interval, associated to the estimated dose, should contain the physical dose delivered to the sample Oestreicher et al 2016). However, deviations from the statistically approved intervals for the dicentric (DCA), translocation detection by Fluorescence in situ Hybridization (FISH), micronucleus (MN) and Premature Condensed Chromosome (PCC) (Terzoudi et al 2016) assays were observed for a few laboratories, indicating the requirement for training for these partners. Training courses were mainly dedicated to DCA, FISH, MN, cH2AX and PCC assays.…”
Section: Education and Trainingmentioning
confidence: 99%